Dectin-1 Acts as a Non-Classical Receptor of Ang II to Induce Cardiac Remodeling. Issue 6 (9th February 2023) - Ye, Shiju; Huang, He; Han, Xue; Luo, Wu; Wu, Lili; Ye, Yang; Gong, Yingchao; Zhao, Xia; Huang, Weijian; Wang, Yi; Long, Xiaohong; Fu, Guosheng; et al.
Abstract : Background: Cardiac remodeling in heart failure involves macrophage-mediated immune responses. Recent studies have shown that a PRR (pattern recognition receptor) called dectin-1, expressed on macrophages, mediates proinflammatory responses. Whether dectin-1 plays a role in pathological cardiac remodeling is unknown. Here, we identified a potential role of dectin-1 in this disease. Methods: To model aberrant cardiac remodeling, we utilized mouse models of chronic Ang II (angiotensin II) infusion. In this model, we assessed the potential role of dectin-1 through using D1KO (dectin-1 knockout) mice and bone marrow transplantation chimeric mice. We then used cellular and molecular assays to discover the underlying mechanisms of dectin-1 function. Results: We found that macrophage dectin-1 is elevated in mouse heart tissues following chronic Ang II administration. D1KO mice were significantly protected against Ang II–induced cardiac dysfunction, hypertrophy, fibrosis, inflammatory responses, and macrophage infiltration. Further bone marrow transplantation studies showed that dectin-1 deficiency in bone marrow–derived cells prevented Ang II–induced cardiac inflammation and dysfunction. Through detailed molecular studies, we show that Ang II binds directly to dectin-1, causing dectin-1 homodimerization and activating the downstream Syk (spleen tyrosine kinase)/NF-κB (nuclear factor kappa B) signaling pathway to induce expression of inflammatory and chemoattractant factors. Mutagenesis studies identified R184 in the C-type lectin domain to interact with Ang II. Blocking dectin-1 in macrophages suppresses Ang II–induced inflammatory mediators and subsequent intercellular cross talk with cardiomyocytes and fibroblasts. Conclusions: Our study has discovered dectin-1 as a new nonclassical receptor of Ang II and a key player in cardiac remolding and dysfunction. These studies suggest that dectin-1 may be a new target for treating hypertension-related heart failure.